1998
DOI: 10.1021/jp972873u
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Negative Activation Energies in Simple Bimolecular Metathesis Reactions and Some Observations on Too-Fast Reactions

Abstract: A large number of reactions of the type R• + HX and R• + X2 have been reported as having negative activation energies (X = I, Br, Cl). These reactions have none of the behavior of reactions that are expected to have negative activation energies. It is shown that they must be simple metathesis reactions having a single transition state, (R·H·Ẋ)⧧ or (R·X·Ẋ)⧧. It is concluded that the negative activation energies must be artifacts of the experimental techniques employed. Some of what appear to be simple metathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 49 publications
(58 reference statements)
3
69
1
Order By: Relevance
“…The function of this chemistry might be to form reactive intermediates next to the antigen that would react with it to nick the protein recognized by the Ab, making it more susceptible to attack by other enzymes in the macrophage. Alternatively, the function of the Ab might be as a 1 (32) and in the pulse radiolysis of air-saturated perchloric acid solution (25) (37)(38)(39)(40)(41)(42). This reaction possesses a negative activation barrier (40)(41)(42), but no molecular level mechenistic study has been reported.…”
Section: Summary Of the H2o3 Plus 1 O2 Mechanism (Pathway Ii)mentioning
confidence: 99%
“…The function of this chemistry might be to form reactive intermediates next to the antigen that would react with it to nick the protein recognized by the Ab, making it more susceptible to attack by other enzymes in the macrophage. Alternatively, the function of the Ab might be as a 1 (32) and in the pulse radiolysis of air-saturated perchloric acid solution (25) (37)(38)(39)(40)(41)(42). This reaction possesses a negative activation barrier (40)(41)(42), but no molecular level mechenistic study has been reported.…”
Section: Summary Of the H2o3 Plus 1 O2 Mechanism (Pathway Ii)mentioning
confidence: 99%
“…10 The role of negative activation energies has also been widely discussed in the reactions of hydrocarbon radicals with hydrogen halides and the related reverse reactions. [11][12][13][14][15][16] The reactions of olefins with hydroxyl radical are important in a variety of combustion and atmospheric contexts. For example, the predominant reaction in the atmosphere is electrophilic addition of OH to olefins.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,11-14 These studies had a significant impact on the derived thermochemistry of small hydrocarbon free radicals and the strength of the C-H bonds in hydrocarbons. 1,2,11 These new findings were met with scepticism due to the long-time belief in the nature of these reactions as "simple metathesis" (ref 15 and references therein). Tschuikow-Roux and co-workers 16,17 attempted to explain the negative apparent activation energy for the reaction of CH 3 with HBr based on the theory developed by Mozurkewich and Benson 10 and quantum chemical calculations of the potential energy surface for the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…21 As noted above, they computed a positive barrier to reaction which had to be adjusted to a negative value to match experiment, and they included a simple tunneling correction. Both corrections were criticized by Benson and Dobis, 22 who argued in favor of smaller CH 3 + HBr rate constants with a positive activation energy. Yu and Nyman 23 conducted quantum scattering calculations, which inherently treat tunneling correctly, based on a PES derived with MP2 second-order perturbation theory that yields a positive barrier.…”
Section: Introductionmentioning
confidence: 99%